Kampo, A Japanese Traditional Medicinal System for Psychiatric Conditions: A Narrative Review - Tatsumi, Laina; Suzuki, Takefumi; Yamada, Kazuo; Mimura, Masaru; Uchida, Hiroyuki (Pharmacopsychiatry, 2019)
Introduction Kampo is a Japanese traditional medicinal system and is represented by unity of mind and body. It is originally based upon Chinese traditional medicine but has uniquely developed in Japan.Methods A narrative review on the use of Kampo for psychiatric conditions is provided.Results Kampo formula is a combination of several crude ingredients; most derive from natural plants and some from animals and minerals. These Kampo formulae are widely prescribed in almost all medical disciplines, including psychiatry, in Japan; they have been used for various psychiatric disorders such as dementia, schizophrenia spectrum disorders, mood disorders, anxiety disorders, and personality disorders. Kampo is a versatile traditional medicine with a variety of positive effects on mental states with relatively benign side effect profiles. Kampo formulae can be adjunctively combined with or substituted for the Western psychotropic drugs, which will provide more treatment options to patients with psychiatric conditions.Discussion This review summarizes the current knowledge on Kampo for psychiatric conditions, highlighting a paucity of data and a need for further good-quality evidence on these medications.
Keywords: herbal medicine; Kampo; psychiatric disorder; traditional medicine